A reversible photochromic material and preparation method thereof
By adjusting the proportions of BaO, BaCl2, BaF2 and the contents of Eu2+ and RE3+ in inorganic photochromic materials, the new reversible photochromic materials were synthesized by high-temperature solid phase method, which solved the shortcomings of existing materials in regulating photochromic color and fading time, and achieved the reversible photochromic properties of multi-color changes in a single matrix material under external field regulation.
Patent Information
- Application Number
- CN202211448997.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-18
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2042-11-18
AI Technical Summary
Existing inorganic photochromic materials have shortcomings in regulating photochromic color and fading time, and there are few reports of a single matrix material achieving multi-color changes under external field regulation.
A new reversible photochromic material was synthesized by high-temperature solid phase method, with a chemical formula of 62.5-x-y(aBaO–bBaCl2–cBaF2)–18.75P2O5:xEu2+,yRE3+. By adjusting the ratio of BaO, BaCl2, BaF2 and the content of Eu2+ and RE3+, the photochromic contrast and fading rate of the material were regulated.
The reversible photochromic properties of a single matrix material with multi-color variation under external field control are achieved. The photochromic contrast can exceed 50%, the fading time can be controlled within the range of 10s-30h, and the material has excellent fatigue resistance.
Smart Images

Figure CN116042208B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of inorganic photochromic materials, and in particular relates to a photochromic material and a preparation method thereof. Background Art
[0002] Under certain conditions, a material undergoes a physical or chemical transformation from state A to state B, accompanied by changes in the absorption spectrum in the visible light region, and the color of the material also changes accordingly. Under another specific condition, it undergoes a physical or chemical transformation from state B to state A again, returning to the initial state. If at least one of the two specific conditions is light irradiation, the material can be called a reversible photochromic material. Photochromic materials have considerable application prospects in the fields of anti-counterfeiting encryption, optical refrigeration, and optical information storage.
[0003] Since Firtzsche first observed the photochromic phenomenon of tetraphenyl from colorless to yellow under sunlight in 1867, a series of organic photochromic materials such as azobenzene, diarylethenes, and spiropyran have emerged in the following hundreds of years. Due to their large contrast before and after photochromic change, these materials have been greatly developed in recent years. However, they have serious drawbacks such as environmental toxicity, the inevitable poor thermal stability of organic matter, and poor fatigue resistance.
[0004] Compared with organic photochromic materials, inorganic photochromic materials have significant advantages such as simple synthesis, no environmental toxicity, and good thermal stability. Inorganic photochromic materials are mainly divided into the following three categories: (1) transition metal oxides, such as TiO2, which changes from white to blue after exposure to sunlight. This type of material can produce a large color contrast under light irradiation, but its reversibility is poor and the color change takes a long time [Physical Review Letters 1968, 21 (18), 1331-1334]; (2) ferroelectric oxides, such as Na2O3, which changes from gray to brown after exposure to sunlight as reported by Zhang et al. 0.5 Bi 2.5 Nb2O9:Er 3+ Photochromic materials: This type of material has good fatigue resistance, but the photochromic contrast is less than 30%, the color change phenomenon is weak, and the manufacturing cost is high. The above problems limit its application in actual production [ACS Appl Mater Interfaces 2016, 8(7), 4789-94]; (3) New rigid network structure photochromic materials, such as Ba5(PO4)3Cl:Eu that Hu et al. reported to be pink in photochromic state. 2+There is no report that the reflectivity difference before and after the color change of this type of material is greater than 30% [ECS SolidState Letters 2012,1(1),R1-R3]; the method of regulating the photochromic color in this type of material is generally to dissolve alkali metal ions or alkaline earth metal ions in the Ba lattice to achieve the purpose of changing the band gap of the material and thus changing the trap depth and thus changing the photochromic color. For example, Hu et al. reported Sr3GdNa(PO4)3F:Eu 2+ Photochromic materials change color from white to sky blue after light irradiation [Sensors and Actuators B:Chemical 2017,245,256-262]; there are no reports on changing the color and fading time of photochromic materials by adjusting temperature and anion doping concentration, and there are no reports on achieving adjustable photochromic color of a single matrix material under external field regulation. Summary of the invention
[0005] The technical problem to be solved by the present invention is to overcome the deficiencies and defects mentioned in the above background technology and provide a single-matrix multi-color adjustable high-performance reversible photochromic material and a preparation method thereof.
[0006] In order to solve the above technical problems, the technical solution proposed by the present invention is:
[0007] A reversible photochromic material with a chemical formula of 62.5-xy(aBaO–bBaCl2–cBaF2)–18.75P2O5:xEu 2+ ,yRE 3+ , wherein 0.3≤a≤0.85, 0.15≤b≤0.5, 0<c≤0.2, 0.125≤x≤1.25, 0≤y≤1.25, the sum of a, b, and c is 1.0, and the values are all molar amounts.
[0008] Preferably, in the chemical formula of the reversible photochromic material, the raw material of BaO includes one or more of barium carbonate, barium acetate, barium oxalate, barium hydroxide, barium phosphate, barium chloride and barium fluoride; the raw material of BaCl2 includes barium chloride and / or a compound of BaO and ammonium chloride; the raw material of BaF2 includes barium fluoride and / or a compound of BaO and ammonium fluoride; the raw material of P2O5 includes one or more of barium phosphate, diammonium phosphate and diammonium hydrogen phosphate; 2+ The raw materials include one or more of europium oxide, europium nitrate, europium acetate, europium oxalate, europium phosphate and europium chloride; the RE 3+ Y 3+ ,La 3+ 、Ce 3+ , Pr 3+ 、Nd 3+ 、Sm3+ , Gd 3+ , Tb 3+ 、Dy 3+ 、Ho 3+ , Er 3+ 、Tm 3+ , Yb 3+ He Lu 3+ One or more of, more preferably Ce 3+ ;RE 3+ The raw materials include one or more of oxides, nitrates, acetates, oxalates, phosphates and chlorides containing RE elements.
[0009] Preferably, after being irradiated with short-wave ultraviolet light or X-rays, the reversible photochromic material changes color from white to any one of purple, purple-red, pink and red.
[0010] Preferably, the color change contrast is calculated as the difference between the absorption intensity at the maximum absorption wavelength after the material changes color and the absorption intensity at the wavelength before the color change. The reversible photochromic material preferably has a sample body color that changes from white to purple, and the sample photochromic contrast is greater than 35%; the sample body color changes from white to purple-red, and the sample photochromic contrast is greater than 50%; the sample body color changes from white to pink, and the sample photochromic contrast is greater than 25%; the sample body color changes from white to red, and the sample photochromic contrast is greater than 35%.
[0011] Preferably, the reversible photochromic material is stored in a dark environment after changing color, and the photochromic contrast remains unchanged at room temperature.
[0012] Preferably, after the reversible photochromic material changes color, it is irradiated with near-ultraviolet-visible light or heat-treated at a temperature above 200°C, and the body color gradually returns to white. Depending on the fading treatment conditions, the fading time is 10s-30h; the photochromic-reversible fading process can be repeated without loss.
[0013] Preferably, the reversible photochromic material with purple or purple-red photochromism fades to pink or white when irradiated with near-ultraviolet-visible light or treated with heat; the reversible photochromic material with red photochromism fades to any one of yellow, yellow-green and white when irradiated with near-ultraviolet-visible light or treated with heat.
[0014] A method for preparing a reversible photochromic material comprises: adopting a high-temperature solid phase method to synthesize the reversible photochromic material by subjecting the raw materials of the reversible photochromic material to high-temperature solid phase calcination.
[0015] Preferably, the high temperature solid phase method is carried out under a weak reducing atmosphere, with a calcination temperature of 1000-1400°C and a calcination time of 3-5 hours; the weak reducing atmosphere can be provided by any one of a mixed gas of H2 / N2, CO / CO2 or H2 / Ar. The reaction conditions of the high temperature solid phase method are conducive to controllably adjusting the defect type and defect distribution in the material, so as to realize and controllably adjust the color change performance of the material.
[0016] When the c, x, y values are fixed and the reaction temperature is 1000-1400℃ and the reaction is carried out for 3-5h under weak reducing atmosphere, the obtained photochromic material absorbs in the range of 430-800nm after irradiation with short-wave ultraviolet light or X-rays, and reaches the absorption peak near 540nm. The sample body color changes from white to purple, purple-red or pink. As b increases from 0.15 to 0.50, the photochromic contrast shows a trend of increasing first and then decreasing.
[0017] When the values of b, c, and y are fixed and the reaction temperature is 1000-1400℃ and the reaction is carried out for 3-5 hours under weak reducing atmosphere, the obtained photochromic material absorbs in the range of 430-800nm and reaches the absorption peak near 540nm after irradiation with short-wave ultraviolet light or X-rays, and the sample body color changes from white to purple, purple-red or pink. As x increases from 0.125 to 1.25, the photochromic contrast shows a trend of increasing first and then decreasing.
[0018] When the b, x, and y values are fixed and the reaction temperature is 1100±30℃ and the reaction is carried out for 3–5h under weak reducing atmosphere, the obtained photochromic material absorbs in the range of 430–800nm after irradiation with short-wave ultraviolet light or X-rays, and reaches the absorption peak at 545nm. The sample body color changes from white to purple, and the photochromic contrast reaches the peak value in the range of c=0.02–0.05, which is not less than 30%. After the material changes color, it shows a time-dependent fading phenomenon under near-ultraviolet-visible light irradiation or thermal stimulation above 200℃. As the fading time increases, the sample body color changes from purple to pink and finally fades to white.
[0019] When the b, x, and y values are fixed and the reaction temperature is 1200±30℃ and the reaction is carried out for 3–5h under weak reducing atmosphere, the obtained photochromic material absorbs in the range of 430–800nm after irradiation with short-wave ultraviolet light or X-rays, and reaches the absorption peak at 545nm. The sample body color changes from white to dark purple, and the photochromic contrast reaches the peak value in the range of c=0.02–0.05, which is not less than 35%. After the material changes color, it shows a time-dependent fading phenomenon under near-ultraviolet-visible light irradiation or thermal stimulation above 200℃. As the fading time increases, the sample body color changes from purple to pink and finally fades to white.
[0020] When the b, x, and y values are fixed and the reaction temperature is 1250±30℃ and the reaction is carried out for 3–5h under weak reducing atmosphere, the obtained photochromic material absorbs in the range of 430–700nm after irradiation with short-wave ultraviolet light or X-rays, and reaches the absorption peak at 540nm. The sample body color changes from white to purple-red, and the photochromic contrast reaches the peak value in the range of c=0.02–0.05, which is not less than 50%. After the material changes color, it shows a time-dependent fading phenomenon under near-ultraviolet-visible light irradiation or thermal stimulation above 200℃. As the fading time increases, the sample body color changes from purple-red to pink, and finally fades to white.
[0021] When the b, x, and y values are fixed and the reaction temperature is 1300±30℃ and the reaction is carried out for 3–5h under weak reducing atmosphere, the obtained photochromic material absorbs in the range of 430–650nm and reaches the absorption peak at 535nm after irradiation with short-wave ultraviolet light or X-rays. The sample body color changes from white to pink, and the photochromic contrast reaches the peak value in the range of c=0.02–0.05, which is not less than 25%. After the material changes color, it shows a time-dependent fading phenomenon under near-ultraviolet-visible light irradiation or thermal stimulation above 200℃. As the fading time increases, the sample body color changes from pink to light pink and finally fades to white.
[0022] Preferably, the high temperature solid phase method adopts a segmented synthesis, specifically:
[0023] (1) React at 1000–1400°C in a weak reducing atmosphere for 3–5 hours;
[0024] (2) reheating at 800–1000°C in air atmosphere for 1–3 h;
[0025] (3) React at 1000–1400°C in a weak reducing atmosphere for 3–5 hours.
[0026] By using a segmented high-temperature solid-phase method, the defect distribution in the material can be further controlled, the color-changing properties can be adjusted, and a reversible photochromic material with multiple absorption peaks can be obtained.
[0027] After short-wave ultraviolet light or X-ray irradiation, the reversible photochromic material synthesized by the high-temperature solid-phase method produces absorption in the range of 430-640nm, reaches absorption peaks at 450 and 535nm, and changes its body color from white to red. The photochromic contrast is not less than 35%. By using near-ultraviolet-visible light irradiation or heat treatment, controlling the light wavelength, heating temperature and treatment time, the body color of the material can be controlled to fade to any one of yellow, yellow-green and white. After the body color of the material stays in yellow or yellow-green, it can still be irradiated with near-ultraviolet-visible light or heat treated to continue fading to white, realizing the color tunability of the photochromic color of a single matrix material under external field regulation.
[0028] Its controllable fading operation includes but is not limited to the following methods:
[0029] Method (1): At room temperature, the discolored material is subjected to light fading treatment, and 532nm green laser (power 3W, hereinafter referred to as "green light") is used for irradiation for 1-5s, and the material body color fades to yellow; 532nm green light is continued to be used for 10s or more, and the material body color fades to yellow-green; then 450nm blue laser (power 3W, hereinafter referred to as "blue light") is used for irradiation for 10-20s, and the material body color fades completely and returns to white;
[0030] Method (2): At room temperature, the discolored material is subjected to light fading treatment. Under visible light irradiation, the material body color gradually fades to yellow, and then to yellow-green, and the fading time varies from 0.5 to 24 hours. The sample body color is reversibly restored to white by continuous irradiation with a white light LED (power 1W, vertical distance 5cm) for more than 2 hours (the white light LED power and irradiation method are the same below and will not be specified again);
[0031] Method (3): Under natural light, the discolored material is subjected to a heating and fading treatment. The temperature is raised from room temperature to 150°C and retained for more than 2 minutes. The sample body color fades to yellow. The temperature is further raised to 200°C and retained for more than 2 minutes. The sample body color fades to yellow-green. The temperature is further raised to 250°C and above and retained for more than 2 minutes. The sample body color fades completely and returns to white.
[0032] Compared with the prior art, the present invention has the following beneficial effects:
[0033] (1) After all the reversible photochromic materials of the present invention change color, the color contrast can be kept unchanged at room temperature or dark conditions; when irradiated with near-ultraviolet-visible light or subjected to heat treatment above 200°C, the coloring-fading process can be repeated multiple times without material performance degradation, indicating that the reversible photochromic materials have excellent fatigue resistance.
[0034] (2) By regulating the composition ratio and synthesis conditions, the color change contrast and fading rate can be precisely controlled. The photochromic contrast of the sample is preferably greater than 50%, and the fading time of the sample after color change can be controlled and adjusted within the range of 10s-30h as the light or heating conditions change. In particular, the color-changing sample can produce 2 or more absorption peaks or changes in the absorption wavelength range, and has the reversible photochromic property of multi-color change of a single matrix under external field regulation. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0036] Figure 1 : The UV-visible diffuse reflectance spectrum of the reversible photochromic material described in Example 1;
[0037] Figure 2 : The UV-visible diffuse reflectance spectrum of the reversible photochromic material described in Example 2;
[0038] Figure 3 : The UV-visible diffuse reflectance spectrum of the reversible photochromic material described in Example 3;
[0039] Figure 4 : The UV-visible diffuse reflectance spectrum of the reversible photochromic material described in Example 4;
[0040] Figure 5 : The UV-visible diffuse reflectance spectrum of the reversible photochromic material described in Example 5;
[0041] Figure 6 : Color change-fading anti-fatigue test results of the reversible photochromic material described in Example 5;
[0042] Figure 7 : The UV-visible diffuse reflectance spectrum of the reversible photochromic material described in Example 6;
[0043] Figure 8 : The UV-visible diffuse reflectance spectrum of the reversible photochromic material described in Example 7;
[0044] Fig. 9 : The UV-visible diffuse reflectance spectrum of the reversible photochromic material described in Example 8;
[0045] Fig.10 : The UV-visible diffuse reflectance spectrum of the reversible photochromic material described in Example 9;
[0046] Fig.11 : The UV-visible diffuse reflectance spectrum of the reversible photochromic material described in Example 10;
[0047] Fig.12 : The UV-visible diffuse reflectance spectrum of the reversible photochromic material described in Example 11;
[0048] Fig.13 : The UV-visible diffuse reflectance spectrum of the reversible photochromic material described in Example 12;
[0049] Fig.14 : The UV-visible diffuse reflectance spectrum of the reversible photochromic material described in Example 13;
[0050] Fig.15 : The UV-visible diffuse reflectance spectrum of the reversible photochromic material described in Example 14;
[0051] Fig.16 : The UV-visible diffuse reflectance spectrum of the reversible photochromic material described in Example 15;
[0052] Fig.17 : The UV-visible diffuse reflectance spectrum of the reversible photochromic material described in Example 16;
[0053] Fig.18 : The UV-visible diffuse reflectance spectrum of the reversible photochromic material described in Example 17;
[0054] Fig.19 : UV-visible diffuse reflectance spectrum of the reversible photochromic material described in Example 18. DETAILED DESCRIPTION
[0055] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the present invention, but the protection scope of the present invention is not limited to the following specific embodiments.
[0056] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.
[0057] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.
[0058] Embodiment 1:
[0059] 43.003125BaO–18.5625BaCl2–0.309375BaF2–18.75P2O5:0.25Eu 2+ ,0.375Ce 3+ Reversible photochromic materials
[0060] The product is synthesized by a high-temperature solid-phase method. Accurately weigh 0.8486g BaCO3, 0.4534g BaCl2·2H2O, 0.0054g BaF2, 0.4313g NH4H2PO4, 0.0044g Eu2O3 and 0.0122g Ce(NO3)3, place the raw materials in a mortar and grind them for about 30 minutes. After mixing evenly, put them into a corundum crucible and react at 1100°C for 3 hours under a weak reducing atmosphere with a volume ratio of H2:Ar=10%:90%; then stop heating, cool to room temperature and grind to obtain a reversible photochromic material product.
[0061] The reversible photochromic material is white in color under natural light (CIE color coordinates L*a*b*: 88.76, 1.52, -0.88). After being irradiated with 254nm ultraviolet light for 1 minute, the color changes to purple (L*a*b*: 82.89, 4.89, -8.96). The ultraviolet-visible diffuse reflectance spectrum of the material produces absorption in the range of 430-800nm and reaches an absorption peak near 560nm. The color change contrast is 11.30%. Its diffuse reflectance spectrum is as follows: Figure 1 After the discolored material was irradiated by a white light LED at close range for 2 minutes, the UV-visible diffuse reflectance spectrum absorption range of the product was reduced to 430-700nm, and the absorption peak was reached near 560nm. The sample body color turned pink (L*a*b*: 87.79, 3.29, -0.54), and its diffuse reflectance spectrum was as shown in the figure below. Figure 1 The discolored material can be restored to its initial state after irradiation with 395nm near-ultraviolet light for 10s. Its diffuse reflectance spectrum is shown in Figure 1 In addition, the material can be restored to its initial state by heat treatment at 250℃ for 2 minutes or placed under natural light for 4 hours. The discoloration-fading process of the reversible photochromic material can be repeated many times, and it has good anti-fatigue performance.
[0062] Embodiment 2:
[0063] 42.075BaO–18.5625BaCl2–1.2375BaF2–18.75P2O5:0.25Eu 2+ ,0.375Ce 3+ Reversible photochromic materials
[0064] The product is synthesized by a high-temperature solid-phase method. 0.8303g BaCO3, 0.4443g BaCl2·2H2O, 0.0217g BaF2, 0.4313g NH4H2PO4, 0.0065g EuCl3 and 0.0066g CeO2 are accurately weighed, the raw materials are placed in a mortar and ground for about 30 minutes, and after mixing evenly, they are loaded into a corundum crucible and reacted at 1100°C for 3 hours under a weak reducing atmosphere with a volume ratio of H2:N2=10%:90%; then the heating is stopped, and the reversible photochromic material product is obtained after grinding after cooling to room temperature.
[0065] The reversible photochromic material is white in color under natural light (L*a*b*: 89.25, 1.36, -4.07). After being irradiated with 254nm ultraviolet light for 1 minute, the color changes to purple (L*a*b*: 82.02, 5.70, -7.09). The UV-visible diffuse reflectance spectrum of the material produces absorption in the range of 430-800nm and reaches an absorption peak near 545nm. The color change contrast is 30.30%. Its diffuse reflectance spectrum is as follows: Figure 2 After the discolored material was irradiated by a white light LED at close range for 2 minutes, the UV-visible diffuse reflectance spectrum absorption range of the product was reduced to 430-700nm, and the absorption peak was reached near 545nm. The sample body color turned pink (L*a*b*: 89.01, 3.86, -1.34). Its diffuse reflectance spectrum is shown in Figure 2 The discolored material can be restored to its original state after heat treatment at 250℃ for 2 minutes. Its diffuse reflectance spectrum is shown in Figure 2 In addition, the sample can be restored to its initial state by irradiating with 395nm near-ultraviolet light for 10s or placing it under natural light for 16h. The discoloration-fading process of the reversible photochromic material can be repeated many times, and it has good anti-fatigue performance.
[0066] Embodiment 3:
[0067] 30.9375BaO–18.5625BaCl2–12.375BaF2–18.75P2O5:0.25Eu 2+ ,0.375Ce 3+ Reversible photochromic materials
[0068] The product is synthesized by a high-temperature solid-phase method. Accurately weigh 0.6105g BaCO3, 0.4534g BaCl2·2H2O, 0.2170g BaF2, 0.4971g (NH4)2HPO4, 0.0044g Eu2O3 and 0.0066g CeO2, place the raw materials in a mortar and grind them for about 30 minutes. After mixing evenly, put them into a corundum crucible and react at 1100°C for 3 hours under a CO / CO2 weak reducing atmosphere. Then stop heating, cool to room temperature and grind to obtain a reversible photochromic material product.
[0069] The reversible photochromic material is white in color (L*a*b*: 90.70, 0.24, -2.47) under natural light, and changes to purple (L*a*b*: 84.69, 4.09, -7.90) after irradiation with 254nm ultraviolet light for 1 minute. The UV-visible diffuse reflectance spectrum of the material produces absorption in the range of 430-800nm and reaches an absorption peak near 545nm. The color change contrast is 31.85%. Its diffuse reflectance spectrum is as follows: Figure 3 After the discolored material was irradiated by a white light LED at close range for 2 minutes, the UV-visible diffuse reflectance spectrum absorption range of the product was reduced to 430-700nm, and the absorption peak was reached near 545nm. The sample body color turned pink (L*a*b*: 88.91, 3.59, -1.90), and its diffuse reflectance spectrum was as shown in the figure below. Figure 3 The discolored material can be restored to its original state after being placed under natural light for 16 hours. Its diffuse reflectance spectrum is shown in Figure 3 In addition, 395nm near-ultraviolet irradiation for 10s or 250℃ heat treatment for 2min can also restore the sample to its initial state. The discoloration-fading process of the reversible photochromic material can be repeated many times, and it has good anti-fatigue performance.
[0070] Embodiment 4:
[0071] 42.075BaO–18.5625BaCl2–1.2375BaF2–18.75P2O5:0.25Eu 2+ ,0.375Ce 3+ Reversible photochromic materials
[0072] The product is synthesized by a high-temperature solid-phase method. 0.8303g BaCO3, 0.4397g BaCl2·2H2O, 0.0217g BaF2, 0.4313g NH4H2PO4, 0.0044g Eu2O3 and 0.0092g CeCl3 are accurately weighed, the raw materials are placed in a mortar and ground for about 30 minutes, and after mixing evenly, they are loaded into a corundum crucible and reacted at 1200°C for 3 hours under a weak reducing atmosphere with a volume ratio of H2:Ar=10%:90%; then the heating is stopped, and the reversible photochromic material product is obtained after grinding after cooling to room temperature.
[0073] The reversible photochromic material is white in natural light (L*a*b*: 93.36, 1.30, -2.67), and changes to purple (L*a*b*: 83.59, 7.07, -7.56) after 1 minute of X-ray irradiation. The UV-visible diffuse reflectance spectrum of the material absorbs in the range of 430-800nm and reaches an absorption peak near 545nm. The color change contrast is 35.42%. Figure 4 As shown. After the discolored material was irradiated by a white light LED at close range for 2 minutes, the absorption range of the product's UV-visible diffuse reflectance spectrum narrowed, and the sample body color turned pink (L*a*b*: 92.79, 2.06, -0.81). The discolored material can be restored to its initial state after being placed in natural light for 20 hours; in addition, irradiation with 450nm blue light for 10s or heat treatment at 250℃ for 2min can also restore the sample to its initial state. The discoloration-fading process of this reversible photochromic material can be repeated many times, and it has good anti-fatigue performance.
[0074] Embodiment 5:
[0075] 42.075BaO–18.5625BaCl2–1.2375BaF2–18.75P2O5:0.25Eu 2+ ,0.375Ce 3+ Reversible photochromic materials
[0076] The product is synthesized by a high-temperature solid-phase method. Accurately weigh 0.8303g BaCO3, 0.4534g BaCl2·2H2O, 0.0217g BaF2, 0.4313g NH4H2PO4, 0.0112g Eu(NO3)3·6H2O and 0.0066g CeO2, place the raw materials in a mortar and grind them for about 30 minutes. After mixing evenly, put them into a corundum crucible and react at 1250°C for 3 hours under a weak reducing atmosphere with a volume ratio of H2:N2=10%:90%. Then stop heating, cool to room temperature and grind to obtain a reversible photochromic material product.
[0077] The reversible photochromic material is white in color under natural light (L*a*b*: 93.41, 0.96, -2.15). After being irradiated with 254nm ultraviolet light for 1 minute, the color changes to purple-red (L*a*b*: 82.62, 11.20, -5.82). The UV-visible diffuse reflectance spectrum of the material produces absorption in the range of 430-750nm and reaches an absorption peak near 540nm. The color change contrast is 44.73%. Its diffuse reflectance spectrum is as follows: Figure 5 As shown. After the discolored material was irradiated with a white light LED at close range for 2 minutes, the absorption range of the product's UV-visible diffuse reflectance spectrum narrowed, and the sample body color turned pink (L*a*b*: 93.72, 2.26, -1.61). The discolored material can be restored to its original state after being irradiated with 450nm blue light for 10 seconds; in addition, the sample can be restored to its original state by being placed under natural light for 24 hours or heat-treated at 250℃ for 2 minutes. The discoloration-fading process of the reversible photochromic material can be repeated many times, and it has good anti-fatigue properties. The reversible discoloration anti-fatigue test results are shown as follows. Figure 6 shown.
[0078] Embodiment 6:
[0079] 40.218BaO–18.5625BaCl2–3.09375BaF2–18.75P2O5:0.25Eu 2+ ,0.375Ce 3+ Reversible photochromic materials
[0080] The product is synthesized by a high-temperature solid-phase method. Accurately weigh 0.7937g BaCO3, 0.4534g BaCl2·2H2O, 0.0542g BaF2, 0.4313g NH4H2PO4, 0.0044g Eu2O3 and 0.0066g CeO2, place the raw materials in a mortar and grind them for about 30 minutes. After mixing evenly, put them into a corundum crucible and react at 1250°C for 5 hours under a weak reducing atmosphere with a volume ratio of H2:N2=10%:90%. Then stop heating, cool to room temperature and grind to obtain a reversible photochromic material product.
[0081] The reversible photochromic material is white in color under natural light (L*a*b*: 97.73, -0.81, -1.12). After being irradiated with 254nm ultraviolet light for 1 minute, the color changes to purple-red (L*a*b*: 81.90, 16.95, -6.54). The UV-visible diffuse reflectance spectrum of the material produces absorption in the range of 430-750nm and reaches an absorption peak near 540nm. The color change contrast is 53.12%. Its diffuse reflectance spectrum is as follows: Figure 7As shown. After the discolored material was irradiated by a white light LED at close range for 2 minutes, the absorption range of the product's UV-visible diffuse reflectance spectrum narrowed, and the sample body color turned pink (L*a*b*: 89.45, 7.35, -3.32). The discolored material can be restored to its initial state after irradiation with 450nm blue light for 20 seconds; in addition, the sample can be restored to its initial state by being placed in natural light for 30 hours or heat-treated at 250℃ for 2 minutes. The discoloration-fading process of this reversible photochromic material can be repeated many times, and it has good anti-fatigue performance.
[0082] Embodiment 7:
[0083] 42.075BaO–18.5625BaCl2–1.2375BaF2–18.75P2O5:0.25Eu 2+ ,0.375Ce 3+ Reversible photochromic materials
[0084] The product is synthesized by a high-temperature solid-phase method. Accurately weigh 0.8303g BaCO3, 0.4534g BaCl2·2H2O, 0.0217g BaF2, 0.4313g NH4H2PO4, 0.0044g Eu2O3 and 0.0066g CeO2, place the raw materials in a mortar and grind them for about 30 minutes. After mixing evenly, put them into a corundum crucible and react at 1300°C for 3 hours under a CO / CO2 weak reducing atmosphere. Then stop heating, cool to room temperature and grind to obtain a reversible photochromic material product.
[0085] The reversible photochromic material is white in color under natural light (L*a*b*: 93.44, 0.66, -0.60). After being irradiated with 254nm ultraviolet light for 1 minute, the color changes to pink (L*a*b*: 90.22, 5.04, -0.28). The UV-visible diffuse reflectance spectrum of the material produces absorption in the range of 430-650nm and reaches an absorption peak near 535nm. The color change contrast is 28.03%. Its diffuse reflectance spectrum is as follows: Figure 8 As shown. After the discolored material was irradiated by a white light LED at close range for 2 minutes, the absorption range of the UV-visible diffuse reflectance spectrum of the product was reduced, and the sample body color turned light pink (L*a*b*: 92.78, 2.26, -0.21). The discolored material can be restored to its initial state after heat treatment at 250℃ for 2 minutes; in addition, the sample can be restored to its initial state by placing it under natural light for 14 hours or irradiating it with 450nm blue light for 10 seconds. The discoloration-fading process of this reversible photochromic material can be repeated many times, and it has good anti-fatigue performance.
[0086] Embodiment 8:
[0087] 41.45625BaO–18.5625BaCl2–1.85625BaF2–18.75P2O5:0.25Eu 2+ ,0.375Ce 3+ Reversible photochromic materials
[0088] The product is synthesized by a high-temperature solid-phase method. Accurately weigh 0.8181g BaCO3, 0.4534g BaCl2·2H2O, 0.0325g BaF2, 0.4313g NH4H2PO4, 0.0112g Eu(NO3)3·6H2O and 0.0122g Ce(NO3)3, place the raw materials in a mortar and grind them for about 30 minutes. After mixing evenly, put them into a corundum crucible and react at 1250°C for 3 hours under a weak reducing atmosphere with a volume ratio of H2:Ar=10%:90%; grind the material after it is cooled to room temperature, and then place it in a corundum crucible and react at 800°C in an air atmosphere for 1 hour; finally, react at a temperature of 1200°C in a weak reducing atmosphere for 3 hours, and grind the material after it is cooled to room temperature to obtain a reversible photochromic material product.
[0089] The reversible photochromic material is white in color under natural light (L*a*b*: 92.35, 0.29, -0.33). After being irradiated with 254nm ultraviolet light for 1 minute, the color changes to red (L*a*b*: 78.78, 16.03, 3.30). The UV-visible diffuse reflectance spectrum of the material produces absorption in the range of 430-640nm, and two absorption peaks appear near 450 and 535nm. The color change contrast in the green light region is 37.20%. Its diffuse reflectance spectrum is as follows: Fig. 9 After the discolored material was irradiated with 532nm green light for 5s, the UV-visible diffuse reflectance spectrum absorption range of the material was reduced to 430-570nm, and the sample body color turned yellow (L*a*b*: 91.70, -0.39, 12.76). Its diffuse reflectance spectrum is shown in Fig. 9 As shown; in addition, the same effect can be achieved by placing the discolored material under natural light for 0.5h or heat treating it at 150℃ for 3min. After the discolored material is irradiated with 532nm green light for 10s, the UV-visible diffuse reflectance spectrum absorption range of the material is further narrowed to 430-500nm, and the sample body color becomes yellow-green (L*a*b*: 91.39, -2.07, 10.73). Its diffuse reflectance spectrum is shown in Fig. 9 As shown; In addition, the same effect can be achieved by placing the discolored material under natural light for 24 hours or heat treating it at 200℃ for 3 minutes. The discolored material can be restored to its initial state after being irradiated with 450nm blue light for 10 seconds. Its diffuse reflectance spectrum is shown in Fig. 9In addition, heat treatment at 250℃ for 2min or white light LED irradiation for 2h can also restore the sample to its initial state. The discoloration-fading process of the reversible photochromic material can be repeated many times, and it has good anti-fatigue performance.
[0090] Example 9
[0091] 42.075BaO–18.5625BaCl2–1.2375BaF2–18.75P2O5:0.25Eu 2+ ,0.375Ce 3+ Reversible photochromic materials
[0092] The product is synthesized by a high-temperature solid-phase method. Accurately weigh 0.0866g BaCO3, 0.1986g NH4Cl, 0.0217g BaF2, 1.1286g Ba3(PO4)2, 0.0044g Eu2O3 and 0.0122g Ce(NO3)3, place the raw materials in a mortar and grind them for about 30 minutes. After mixing evenly, put them into a corundum crucible and react at 1200°C for 3 hours under a weak reducing atmosphere with a volume ratio of H2:N2=10%:90%; then stop heating, cool to room temperature and grind to obtain a reversible photochromic material product.
[0093] The reversible photochromic material is white in natural light and changes to purple after 1 minute of X-ray irradiation. The UV-visible diffuse reflectance spectrum of the material absorbs in the range of 430-800nm and reaches an absorption peak near 545nm. The color change contrast is 10.89%. Fig.10 As shown. After the discolored material was irradiated by a white light LED at close range for 2 minutes, the absorption range of the UV-visible diffuse reflectance spectrum of the product was reduced, and the sample body color turned pink. The discolored material can be restored to its initial state after heat treatment at 250℃ for 2 minutes; in addition, the sample can be restored to its initial state by placing it under natural light for 4 hours or irradiating it with 450nm blue light for 10 seconds. The discoloration-fading process of this reversible photochromic material can be repeated many times, and it has good anti-fatigue performance.
[0094] Example 10
[0095] 42.075BaO–18.5625BaCl2–1.2375BaF2–18.75P2O5:0.25Eu 2+ ,0.375Ce 3+ Reversible photochromic materials
[0096] The product is synthesized by a high-temperature solid-phase method. 0.8547g BaCO3, 0.4397g BaCl2·2H2O, 0.0092g NH4F, 0.4313g NH4H2PO4, 0.0044g Eu2O3 and 0.0092g CeCl3 are accurately weighed, the raw materials are placed in a mortar and ground for about 30 minutes, and after mixing evenly, they are loaded into a corundum crucible and reacted at 1250°C for 3 hours under a weak reducing atmosphere with a volume ratio of H2:Ar=10%:90%; then the heating is stopped, and the reversible photochromic material product is obtained by grinding after cooling to room temperature.
[0097] The reversible photochromic material is white under natural light, and changes to purple-red after being irradiated with 254nm ultraviolet light for 1 minute. The ultraviolet-visible diffuse reflectance spectrum of the material produces absorption in the range of 430-700nm and reaches an absorption peak near 540nm. The color change contrast is 8.76%. Fig.11 As shown. After the discolored material was irradiated by a white light LED at close range for 2 minutes, the absorption range of the UV-visible diffuse reflectance spectrum of the product was reduced, and the sample body color turned pink. The discolored material can be restored to its initial state after being placed in natural light for 3 hours; in addition, the sample can also be restored to its initial state by heat treatment at 250℃ for 2 minutes or irradiation with 450nm blue light for 10 seconds. The discoloration-fading process of this reversible photochromic material can be repeated many times, and it has good anti-fatigue performance.
[0098] Embodiment 11:
[0099] 31.0625BaO–18.6375BaCl2–12.425BaF2–18.75P2O5:0.25Eu 2+ ,0.125Y 3+ Reversible photochromic materials
[0100] The product is synthesized by a high-temperature solid-phase method. Accurately weigh 0.6129g BaCO3, 0.4552g BaCl2·2H2O, 0.2178g BaF2, 0.4971g (NH4)2HPO4, 0.0044g Eu2O3 and 0.0034g Y(NO3)3, place the raw materials in a mortar and grind them for about 30 minutes. After mixing evenly, put them into a corundum crucible and react at 1250°C for 3 hours under a CO / CO2 weak reducing atmosphere. Then stop heating, cool to room temperature and grind to obtain a reversible photochromic material product.
[0101] The reversible photochromic material is white under natural light, and changes to purple-red after being irradiated with 254nm ultraviolet light for 1 minute. The ultraviolet-visible diffuse reflectance spectrum of the material absorbs in the range of 430-750nm and reaches an absorption peak near 545nm. The color change contrast is 38.36%. Fig.12 As shown. After the discolored material was irradiated by a white light LED at close range for 2 minutes, the absorption range of the UV-visible diffuse reflectance spectrum of the product was reduced, and the sample body color turned pink. The discolored material can be restored to its initial state after heat treatment at 250℃ for 2 minutes; in addition, the sample can be restored to its initial state by placing it under natural light for 20 hours or irradiating it with 532nm green light for 20 seconds. The discoloration-fading process of this reversible photochromic material can be repeated many times, and it has good anti-fatigue performance.
[0102] Embodiment 12:
[0103] 31.0625BaO–18.6375BaCl2–12.425BaF2–18.75P2O5:0.25Eu 2+ ,0.125Tm 3+ Reversible photochromic materials
[0104] The product is synthesized by a high-temperature solid-phase method. 0.6129g BaCO3, 0.4278g BaCl2·2H2O, 0.2178g BaF2, 0.4313g NH4H2PO4, 0.0065g EuCl3 and 0.0034g TmCl3 are accurately weighed, the raw materials are placed in a mortar and ground for about 30 minutes, and after mixing evenly, they are loaded into a corundum crucible and reacted at 1250°C for 3 hours under a weak reducing atmosphere with a volume ratio of H2:N2=10%:90%; then the heating is stopped, and the reversible photochromic material product is obtained after cooling to room temperature and grinding.
[0105] The reversible photochromic material is white under natural light, and changes to purple-red after being irradiated with 254nm ultraviolet light for 1 minute. The ultraviolet-visible diffuse reflectance spectrum of the material produces absorption in the range of 430-750nm and reaches an absorption peak near 545nm. The color change contrast is 30.06%. Its diffuse reflectance spectrum is as follows: Fig.13 As shown. After the discolored material was irradiated by a white light LED at close range for 2 minutes, the absorption range of the UV-visible diffuse reflectance spectrum of the product was reduced, and the sample body color turned pink. The discolored material can be restored to its initial state after irradiation with 532nm green light for 20 seconds; in addition, the sample can be restored to its initial state by placing it under natural light for 16 hours or heat-treating it at 250℃ for 2 minutes. The discoloration-fading process of this reversible photochromic material can be repeated many times, and it has good anti-fatigue performance.
[0106] Embodiment 13:
[0107] 40.4625BaO–9.3375BaCl2–12.45BaF2–18.75P2O5:0.125Eu 2+ ,0.125Ce 3+ Reversible photochromic materials
[0108] The product is synthesized by a high-temperature solid-phase method. Accurately weigh 0.7984g BaCO3, 0.2280g BaCl2·2H2O, 0.2183g BaF2, 0.4313g NH4H2PO4, 0.0022g Eu2O3 and 0.0022g CeO2, place the raw materials in a mortar and grind them for about 30 minutes. After mixing evenly, put them into a corundum crucible and react at 1300°C for 3 hours under a CO / CO2 weak reducing atmosphere. Then stop heating, cool to room temperature and grind to obtain a reversible photochromic material product.
[0109] The reversible photochromic material is white under natural light and turns pink after being irradiated with 254nm ultraviolet light for 1 minute. The UV-visible diffuse reflectance spectrum of the material absorbs in the range of 430-700nm and reaches an absorption peak near 535nm. The color change contrast is 3.20%. Fig.14 As shown. The discolored material can be restored to its original state after being irradiated with 532nm green light for 10s; in addition, the sample can be restored to its original state by being placed in natural light for 0.5h or heat-treated at 250℃ for 1min. The discoloration-fading process of this reversible photochromic material can be repeated many times, and it has good anti-fatigue performance.
[0110] Embodiment 14:
[0111] 18.675BaO–31.125BaCl2–12.45BaF2–18.75P2O5:0.125Eu 2+ ,0.125Ce 3+ Reversible photochromic materials
[0112] The product is synthesized by a high-temperature solid-phase method. Accurately weigh 0.3685g BaCO3, 0.7603g BaCl2·2H2O, 0.2183g BaF2, 0.4313g NH4H2PO4, 0.0022g Eu2O3 and 0.0040g Ce(NO3)3, place the raw materials in a mortar and grind them for about 30 minutes. After mixing evenly, put them into a corundum crucible and react at 1300°C for 3 hours under a weak reducing atmosphere with a volume ratio of H2:N2=10%:90%. Then stop heating, cool to room temperature and grind to obtain a reversible photochromic material product.
[0113] The reversible photochromic material is white under natural light and turns pink after being irradiated with 254nm ultraviolet light for 1 minute. The UV-visible diffuse reflectance spectrum of the material absorbs in the range of 430-700nm and reaches an absorption peak near 535nm. The color change contrast is 6.70%. Fig.15 As shown. The discolored material can be restored to its original state after heat treatment at 250℃ for 1min; in addition, the sample can be restored to its original state by being placed in natural light for 0.5h or irradiated with 532nm green light for 10s. The discoloration-fading process of this reversible photochromic material can be repeated many times and has good anti-fatigue performance.
[0114] Embodiment 15:
[0115] 31.1875BaO–18.7125BaCl2–12.475BaF2–18.75P2O5:0.125Eu 2+ Reversible photochromic materials
[0116] The product is synthesized by a high-temperature solid-phase method. 0.6155g BaCO3, 0.4570g BaCl2·2H2O, 0.2187g BaF2, 0.4971g (NH4)2HPO4 and 0.0022g Eu2O3 are accurately weighed, the raw materials are placed in a mortar and ground for about 30 minutes, and after being mixed evenly, they are loaded into a corundum crucible and reacted at 1300°C for 3 hours under a weak reducing atmosphere with a volume ratio of H2:Ar=10%:90%; then the heating is stopped, and the reversible photochromic material product is obtained after grinding after cooling to room temperature.
[0117] The reversible photochromic material is white under natural light, and changes color to pink after being irradiated with 254nm ultraviolet light for 1 minute. The UV-visible diffuse reflectance spectrum of the material absorbs in the range of 430-700nm and reaches an absorption peak near 535nm. The color change contrast is 3.35%. Fig.16 As shown. The discolored material can be restored to its original state after being placed in natural light for 0.5 hours; in addition, heat treatment at 250℃ for 1 minute or irradiation with 532nm green light for 10 seconds can also restore the sample to its original state. The discoloration-fading process of this reversible photochromic material can be repeated many times, and it has good anti-fatigue performance.
[0118] Embodiment 16:
[0119] 30.625BaO–18.375BaCl2–12.25BaF2–18.75P2O5:1.25Eu 2+ Reversible photochromic materials
[0120] The product is synthesized by a high-temperature solid-phase method. Accurately weigh 0.6044g BaCO3, 0.4488g BaCl2·2H2O, 0.2148g BaF2, 0.4313g NH4H2PO4 and 0.0557g Eu(NO3)3·6H2O, place the raw materials in a mortar and grind them for about 30 minutes. After mixing evenly, put them into a corundum crucible and react at 1300°C for 3 hours under a weak reducing atmosphere with a volume ratio of H2:N2=10%:90%. Then stop heating, cool to room temperature and grind to obtain a reversible photochromic material product.
[0121] The reversible photochromic material is white under natural light and turns pink after being irradiated with 254nm ultraviolet light for 1 minute. The UV-visible diffuse reflectance spectrum of the material absorbs in the range of 430-700nm and reaches an absorption peak near 535nm. The color change contrast is 2.65%. Fig.17 As shown. The discolored material can be restored to its original state after heat treatment at 250℃ for 1min; in addition, the sample can be restored to its original state by being placed in natural light for 0.5h or irradiated with 532nm green light for 10s. The discoloration-fading process of this reversible photochromic material can be repeated many times and has good anti-fatigue performance.
[0122] Embodiment 17:
[0123] 31.0625BaO–18.6375BaCl2–12.425BaF2–18.75P2O5:0.25Eu 2+ ,0.125Ce 3+ Reversible photochromic materials
[0124] The product is synthesized by a high-temperature solid-phase method. 0.6129g BaCO3, 0.4552g BaCl2·2H2O, 0.2178g BaF2, 0.4313g NH4H2PO4, 0.0044g Eu2O3 and 0.0022g CeO2 are accurately weighed, the raw materials are placed in a mortar and ground for about 30 minutes, and after mixing evenly, they are loaded into a corundum crucible and reacted at 1300°C for 3 hours under a weak reducing atmosphere with a volume ratio of H2:N2=10%:90%; then the heating is stopped, and the reversible photochromic material product is obtained after grinding after cooling to room temperature.
[0125] The reversible photochromic material is white in natural light and turns pink after 1 minute of X-ray irradiation. The UV-visible diffuse reflectance spectrum of the material absorbs in the range of 430-650nm and reaches an absorption peak near 535nm. The color change contrast is 12.75%. Fig.18As shown. The discolored material can be restored to its original state after being irradiated with 532nm green light for 10s; in addition, the sample can be restored to its original state by being placed in natural light for 4h or heat-treated at 250℃ for 2min. The discoloration-fading process of this reversible photochromic material can be repeated many times, and it has good anti-fatigue performance.
[0126] Embodiment 18:
[0127] 30.5BaO–18.3BaCl2–12.2BaF2–18.75P2O5:0.25Eu 2+ ,1.25Ce 3+ Reversible photochromic materials
[0128] The product is synthesized by a high-temperature solid-phase method. 0.6018g BaCO3, 0.4470g BaCl2·2H2O, 0.2139g BaF2, 0.4313g NH4H2PO4, 0.0044g Eu2O3 and 0.0220g CeO2 are accurately weighed, the raw materials are placed in a mortar and ground for about 30 minutes, and after mixing evenly, they are loaded into a corundum crucible and reacted at 1300°C for 3 hours under a weak reducing atmosphere with a volume ratio of H2:N2=10%:90%; then the heating is stopped, and the reversible photochromic material product is obtained after cooling to room temperature and grinding.
[0129] The reversible photochromic material is white in natural light and turns pink after 1 minute of X-ray irradiation. The UV-visible diffuse reflectance spectrum of the material absorbs in the range of 430-650nm and reaches an absorption peak near 535nm. The color change contrast is 14.05%. Fig.19 As shown. The discolored material can be restored to its original state after heat treatment at 250℃ for 2 minutes; in addition, the sample can be restored to its original state by being placed in natural light for 4.5 hours or irradiated with 532nm green light for 10 seconds. The discoloration-fading process of this reversible photochromic material can be repeated many times and has good anti-fatigue performance.
Claims
1. A reversible photochromic material, characterized in that: Its chemical formula is 62.5- x - y ( a BaO– b BaCl2– c BaF2)–18.75P2O5: x Eu 2+ , y RE 3+ , where 0.3≤ a ≤0.85,0.15≤ b ≤0.5,0< c ≤0.2,0.125≤ x ≤1.25,0≤ y ≤1.25, a , b , c The sum is 1.0, the values are all molar amounts, and the RE 3+ Y 3+ 、Ce 3+ and Tm 3+ One or more of .
2. The reversible photochromic material according to claim 1, characterized in that: The raw materials of the reversible photochromic material are specifically as follows: the raw materials of BaO include one or more of barium carbonate, barium acetate, barium oxalate, barium hydroxide, barium phosphate, barium chloride and barium fluoride; the raw materials of BaCl2 include barium chloride and / or a compound of BaO and ammonium chloride; the raw materials of BaF2 include barium fluoride and / or a compound of BaO and ammonium fluoride; the raw materials of P2O5 include one or more of barium phosphate, diammonium phosphate and diammonium hydrogen phosphate; the raw materials of Eu 2+ The raw materials include one or more of europium oxide, europium nitrate, europium acetate, europium oxalate, europium phosphate and europium chloride; RE 3+ The raw materials include one or more of oxides, nitrates, acetates, oxalates, phosphates and chlorides containing RE elements.
3. The reversible photochromic material according to any one of claims 1 or 2, characterized in that: After being irradiated by short-wave ultraviolet light or X-rays, the reversible photochromic material changes color from white to any one of purple, purple-red, pink and red.
4. The reversible photochromic material according to claim 3, characterized in that: When the body color of the reversible photochromic material changes from white to purple, the photochromic contrast of the sample is greater than 35%; when the body color changes from white to purple-red, the photochromic contrast of the sample is greater than 50%; when the body color changes from white to pink, the photochromic contrast of the sample is greater than 25%; when the body color changes from white to red, the photochromic contrast of the sample is greater than 35%.
5. The reversible photochromic material according to claim 3, characterized in that: After the reversible photochromic material changes color, it is irradiated with near-ultraviolet-visible light or heat-treated at a temperature above 200°C, and the body color gradually returns to white, with a fading time of 10s-30h; the photochromic-reversible fading process can be repeated without loss.
6. The reversible photochromic material according to claim 5, characterized in that: The reversible photochromic material with purple or purple-red photochromism fades to pink or white when irradiated with near-ultraviolet-visible light or treated with heat. The reversible photochromic material with red photochromism fades to any one of yellow, yellow-green and white when irradiated with near-ultraviolet-visible light or treated with heat.
7. A method for preparing a reversible photochromic material according to any one of claims 1 to 5, characterized in that: The high-temperature solid-phase method is used to synthesize the reversible photochromic material by calcining the raw materials of the reversible photochromic material through high-temperature solid-phase calcination. The high-temperature solid-phase method is carried out under a weak reducing atmosphere with a calcination temperature of 1000-1400°C and a calcination time of 3-5 h; the weak reducing atmosphere is provided by any one of a mixed gas of H2 / N2, CO / CO2 or H2 / Ar.
8. The preparation method according to claim 7, characterized in that: The high temperature solid phase method adopts a segmented synthesis, specifically: (1) React at 1000–1400 °C in a weak reducing atmosphere for 3–5 h; (2) Reheating at 800–1000 °C in air atmosphere for 1–3 h; (3) React at 1000–1400 °C in a weakly reducing atmosphere for 3–5 h.
9. The preparation method according to claim 8, characterized in that The reversible photochromic material synthesized in a stepwise manner by the high-temperature solid-phase method absorbs in the range of 430-640 nm after being irradiated with short-wave ultraviolet light or X-rays, and reaches two absorption peaks, and the body color changes from white to red. By irradiating with near-ultraviolet-visible light or heat treatment and controlling the conditions of the light or heat treatment, the body color of the material can be controllably faded to yellow, yellow-green and white.